2023
DOI: 10.3390/biomedicines11051245
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Nanoparticles: Their Potential Role in Breast Cancer Immunotherapy via Trained Immunity Provocation

Abstract: Owing to drawbacks in the current common cancer therapies including surgery, chemotherapy and radiotherapy, the development of more reliable, low toxic, cost-effective and specific approaches such as immunotherapy is crucial. Breast cancer is among the leading causes of morbidity and mortality with a developed anticancer resistance. Accordingly, we attempted to uncover the efficacy of metallic nanoparticles (MNPs)-based breast cancer immunotherapy emphasizing trained immunity provocation or innate immunity ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 94 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…Additional molecular analysis of methicillin-and heat-resistant S. aureus (MHRSA) isolates, in particular AGM2 and AFC6, is required. Resistance to high heat treatment by MRSA has been indicated in several previous studies [32,[34][35][36][37]. Cleanliness in primary production, immunization, logistical slaughter, and disinfection procedures should all be used in areas where the frequency of infections has been significant.…”
Section: Resultsmentioning
confidence: 99%
“…Additional molecular analysis of methicillin-and heat-resistant S. aureus (MHRSA) isolates, in particular AGM2 and AFC6, is required. Resistance to high heat treatment by MRSA has been indicated in several previous studies [32,[34][35][36][37]. Cleanliness in primary production, immunization, logistical slaughter, and disinfection procedures should all be used in areas where the frequency of infections has been significant.…”
Section: Resultsmentioning
confidence: 99%
“…The dosimetric advantage of IMRT over 3D-CT has been shown in several investigations; some of these trials have revealed reduced doses to the ipsilateral lung, heart, and left anterior descending artery [22]. In this prospective study, we compared the 3D conformal with the DIBH approach, which is considered to be the standard technique for left breast irritation, with the 4D-CT IMRT maximal intensity projection (MIP) plan on patients with left-sided breast cancer [23]. Twenty-five patients were enrolled and performed the procedure while holding their breath for 15 to 20 s and demonstrating high compliance.…”
Section: Discussionmentioning
confidence: 99%
“…As immunology progressed, “Coley toxins” were found to stimulate and regulate the immune system in a multilevel manner—this increased interest in the medicinal potentials of Coley's approach [ 28 ]. Later, several bacterial lysate- or extract-based immunotherapies were developed, including intravesical bacillus Calmette–Guérin (BCG) for in situ bladder carcinoma [ 29 , 30 , 31 ], heat-killed Mycobacterium indicus pranii for invasive bladder cancer and non-small cell lung cancers (NSCLC) [ 32 , 33 ], and heat-killed whole-cell Mycobacterium obuense for melanoma patients [ 34 ].…”
Section: Introductionmentioning
confidence: 99%